2013
DOI: 10.1021/jp403739y
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Assembly, and Particle/Solvent Interactions of Pd Nanoparticles Electrodeposited from a Deep Eutectic Solvent

Abstract: Supported nanoparticle synthesis and assembly have application in a wide range of modern day applications. Key to the manipulation of the particle assembly is an understanding of the interaction between the particles and solvent. Here, we employ a comprehensive in situ approach, together with ex situ SEM imaging, to study supported palladium nanoparticles, electrodeposited from a 2:1 urea:choline Cl– DES. Using cyclic voltammetry, we confirm the expected adsorption of electroactive species onto the deposited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 43 publications
4
58
0
Order By: Relevance
“…Such a system is commonly found in low-crystalline polymers where there is a gradual transition of ρ(r) at the phase boundary [3]. This phenomenon is also found in nanoparticle electrodeposition in deep eutectic solvents [38]. In this study, the observed negative deviations were associated with charge-neutralizing layers above particle ensembles on the surface.…”
Section: Power-law Decayssupporting
confidence: 60%
See 1 more Smart Citation
“…Such a system is commonly found in low-crystalline polymers where there is a gradual transition of ρ(r) at the phase boundary [3]. This phenomenon is also found in nanoparticle electrodeposition in deep eutectic solvents [38]. In this study, the observed negative deviations were associated with charge-neutralizing layers above particle ensembles on the surface.…”
Section: Power-law Decayssupporting
confidence: 60%
“…(6.33). Although this has been used for significantly narrow distributions [37,38,59], there are better ways to properly account for structure in a polydisperse system. One such method, for relatively narrow size distributions, is by using the so-called local monodisperse approximation [60].…”
Section: Size Distribution and Anisotropic Inhomogeneitiesmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The electrodeposition from these non-aqueous baths have proven successful to obtain nickel coatings, [18][19][20]34 nickel-based alloys 21,22,24,25,27,28,35 and nanostructured nickel films for corrosion resistance. 29,30 Similarly, DES were also used for the synthesis of a multitude of nanostructures (Pd, 36 Au, 37 ...), due to the capability of these solvents to slow down the electrochemical processes, thus, having a better control of the deposition of nanostructures. 15 Likewise, DESs are especially interesting because of their ability to stabilize nanoclusters and to facilitate nanoparticle self-assembly without the need for additives and stabilizing agents.…”
Section: Introductionmentioning
confidence: 99%
“…15 Likewise, DESs are especially interesting because of their ability to stabilize nanoclusters and to facilitate nanoparticle self-assembly without the need for additives and stabilizing agents. 36 Both the halide salt and the hydrogen bond donor (HBD) present in the DES, are expected to influence the shape-controlled synthesis of nanomaterials. 38 Moreover, the unavoidable presence of water, due to the hygroscopicity of these media, makes the deposition processes more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Hammons, et al reported electrodeposition of Pd NPs in choline chloride and urea DES. 24 They controlled size of the Pd NPs by controlling temperature; Pd NPs were 10 nm at 32.5…”
mentioning
confidence: 99%